Listening to paediatric primary care nurses: a qualitative study of the potential for interprofessional oral health practice in six federally qualified health centres in Massachusetts and Maryland. Issue 3 (29th March 2017) - Bernstein, Judith; Gebel, Christina; Vargas, Clemencia; Geltman, Paul; Walter, Ashley; Garcia, Raul; Tinanoff, Norman
Abstract : Objectives: To explore the opportunities for interprofessional collaboration (IPC) to improve paediatric oral health in federally qualified health centres (FQHCs), to identify challenges to IPC-led integration of oral health prevention into the well-child visit and to suggest strategies to overcome barriers. Sample: Nurse managers (NMs), nurse practitioners (NPs), paediatric clinical staff and administrators in six FQHCs in two states were interviewed using a semistructured format. Design: Grounded theory research. Topics included feasibility of integration, perceived barriers and strategies for incorporating oral health into paediatric primary care. Measurements: Qualitative data were coded and analysed using NVivo 10 to generate themes iteratively. Results: Nurses in diverse roles recognised the importance of oral health prevention but were unaware of professional guidelines for incorporating oral health into paediatric encounters. They valued collaborative care, specifically internal communication, joint initiatives and training and partnering with dental schools or community dental practices. Barriers to IPC included inadequate training, few opportunities for cross-communication and absence of charting templates in electronic health records. Conclusions: NMs, NPs and paediatric nursing staff all value IPC to improve patients' oral health, yet are constrained by lack of oral health training and supportive charting and referral systems. With supports, they are willing to take on responsibility for introducing oral health preventive measures into the well-child visit, but will require IPC approaches to training and systems changes. IPC teams in the health centre setting can work together, if policy and administrative supports are in place, to provide oral health assessments, education, fluoride varnish application and dental referrals, decrease the prevalence of early childhood caries and increase access to a dental home for low-income children.